Pass or fail? Identifying European best practice regions of university-centered knowledge transfer for sustainability transformations - Thekla Dekkera; Louisa Jantos (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2024)
Sustainability transformation needs regional engagement of the entirety of actors within. One central actor is the university with its mission and activities to transfer knowledge. This paper provides a first approach to identifying best practice regions for sustainability transformation within Europe and addresses potential literature gaps. By composite indexing of systemic sustainability indices and knowledge transfer metrics on a regional level as well as a subsequent systematic literature review, this work aims at (1) providing best practice regions for sustainability transformation and actor collaboration as well as (2) future research avenues. The study selects Copenhagen, Zurich, Stockholm, and Helsinki as regions of interest. It advocates exploring the dynamics within entire regions, emphasizing the interplay of actors in Regional Innovation Systems (RIS). – – Die Transformation in Richtung Nachhaltigkeit erfordert ein regionales Engagement der Gesamtheit der Akteure. Ein zentraler Akteur ist die Universität mit ihrem Auftrag und ihren Aktivitäten des Wissenstransfers. Diese Studie bietet einen ersten Ansatz zur Identifizierung von Best-Practice-Regionen für die Nachhaltigkeitstransformation in Europa und geht auf mögliche Literaturlücken ein. Durch eine zusammengesetzte Indexierung von systemischen Nachhaltigkeitsindizes und Wissenstransfer-Metriken auf regionaler Ebene sowie eine anschließende systematische Literaturrecherche zielt diese Arbeit darauf ab, (1) Best-Practice-Regionen für die Nachhaltigkeitstransformation und die Zusammenarbeit von Akteuren zu identifizieren sowie (2) zukünftige Forschungsansätze zu identifizieren. Die Studie wählt Kopenhagen, Zürich, Stockholm und Helsinki als Regionen von Interesse aus. Sie plädiert dafür, die ganzheitliche Dynamik innerhalb der Regionen zu untersuchen und dabei das Zusammenspiel der Akteure in regionalen Innovationssystemen (RIS) zu betonen.
Keywords: I23; O31; O35; 330; Regional Innovation System; Knowledge Transfer; best practice; Europe; University